Membuktikan dan Menemukan Model Kepimpinan dan Budaya Organisasi Yang Islami - Hamran, Rachmat Ghafur; Harbiah, St; Sudirman, Sudirman; Awaluddin, Murtadi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Leadership and organizational culture from an Islamic perspective are an added value in an organization because its orientation is not only about the world, but also oriented towards the afterlife. The purpose of this study is to see how the model of Islamic leadership and organizational culture. This study uses a library research method, an approach that aims to collect information and data from various library sources. This research process focuses on data from literature, such as history books. Islamic leadership and organizational culture are very helpful for the sustainability of the organization because they can help present positive things in the organization. With this positive impact, it will affect the sustainability of the organization in the long term and can achieve its goals well.